Pengaruh Ukuran Perusahaan, Volume Perdagangan Saham, dan Kebijakan Dividen Terhadap Volatilitas Harga Saham Pada Perusahaan Yang Terdaftar Di Jakarta Islamic Index - Ikhbal Septyaji Putranto Trijasa; Muhammad Sholahuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study examines the impact of firm size, stock trading volume, and dividend policy on stock price volatility in companies listed on the Jakarta Islamic Index (JII) from 2020 to 2023. Using a quantitative approach, the research analyzes 13 firms that consistently remained in JII and dis-tributed dividends, resulting in 52 observations. Panel data regression processed through E-Views 12 is employed to assess relationships between variables. The findings indicate that firm size has a significant negative effect on stock price volatility, whereas trading volume and dividend policy, measured by the Dividend Payout Ratio (DPR), show no significant influence. However, the study is limited by its small sample size, restricted variables, and exclusive focus on JII stocks. Future research should explore additional variables, extend the observation period, and include broader samples beyond JII-listed companies for more comprehensive results.